The Transformation of Aristocratic Landownership in the Eastern Netherlands, c. 1750-1850 - van Cruyningen, Piet (TSEG - The Low Countries Journal of Social and Economic History, 2025)
The Batavian Revolution of 1795 put an end to officeholding in the provinces of Gelderland and Overijssel, as afforded to noblemen through possession of a noble estate. Many indebted noblemen were forced to sell out, and many noble houses were demolished. A small group of wealthy families survived the revolution by increasing revenue from their estates. They even expanded those estates, particularly by using their influence to press for division of the commons and by appropriating large parts of the commons. In this way, a veritable landed elite came into being, which put a strong imprint on the landscape in the sandy regions of the eastern Netherlands.